2007
DOI: 10.1111/j.1574-6941.2007.00285.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of quorum-sensing blockers on the formation of marine microbial communities and larval attachment

Abstract: We studied the effect of the quorum-sensing (QS) blockers 5-hydroxy-3[(1R)-1-hydroxypropyl]-4-methylfuran-2(5H)-one (FUR1), (5R)-3,4-dihydroxy-5-[(1S)-1,2-dihydroxyethyl]furan-2(5H)-one (FUR2) and triclosan (TRI) on the formation of bacterial biofilms, and the effect of these biofilms on the larval attachment of the polychaete Hydroides elegans and the bryozoan Bugula neritina. 14-day-old subtidal biofilms were harvested from artificial substrata and were allowed to develop in the laboratory with and without Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 59 publications
5
57
2
1
Order By: Relevance
“…Anthropogenic pollutants can indirectly impact the EPS secretion pattern by affecting bacterial physiology or by inducing shifts in bacterial species composition. For the antibacterial compound triclosan, it was shown that the pollutant interfered with the quorum sensing signalling of Gram-negative bacteria (direct effect on EPS compounds that are strongly involved in cell communication); as a result, bacterial attachment, growth and the formation of biofilm were significantly hampered (Dobretsov et al 2007). Thus, altering EPS secretion might significantly impair important functionalities of biofilm for the aquatic habitat such as sediment stabilisation (also see Section 2.3).…”
Section: The Significance Of Epsmentioning
confidence: 98%
“…Anthropogenic pollutants can indirectly impact the EPS secretion pattern by affecting bacterial physiology or by inducing shifts in bacterial species composition. For the antibacterial compound triclosan, it was shown that the pollutant interfered with the quorum sensing signalling of Gram-negative bacteria (direct effect on EPS compounds that are strongly involved in cell communication); as a result, bacterial attachment, growth and the formation of biofilm were significantly hampered (Dobretsov et al 2007). Thus, altering EPS secretion might significantly impair important functionalities of biofilm for the aquatic habitat such as sediment stabilisation (also see Section 2.3).…”
Section: The Significance Of Epsmentioning
confidence: 98%
“…TCS inhibits fatty acid synthesis with subsequent perturbation of the bacterial membrane [13] but it also interferes with the quorum-sensing signaling of Gram-negative bacteria; thus inhibiting their attachment, growth and formation of biofilm [46]. In that context, Dobretsov et al [46] reported on the specific sensitivity of Alpha-and Gammaproteobacteria as well as on Cytophagia of the phylum Bacteroidetes to concentrations of TCS of 10 -3 M in contrast to the unaffected Gram-positive phylum of Firmicutes. While in the present experiment Bacteroidetes members were indeed sensitive to TCS, species belonging to the Alphaproteobacteria (Brucellacea/Pseudochrobactrum glaciei) as well as Firmicutes (Carnobacteriaceae/Carnobacterium mobile, C. inhibens) were found solely from samples exposed to high TCS concentrations (T5, 100 mg L -1 ).…”
Section: Bacterial Diversity and Community Composition Under Triclosamentioning
confidence: 99%
“…It was proposed that bacteria might use QS as a weapon to compete for survival or to dominate in a natural niche (Waters and Bassler, 2005;Defoirdt et al, 2008). Indeed, in the laboratory, AHL was shown to mediate the interaction between Pseudomonas aeruginosa and Agrobacterium tumefaciens in biofilm cocultures , whereas AHL-QS blockers and the presence of AHLs were found to change bacterial community composition and function in natural environments and activated sludge (Valle et al, 2004;McLean et al, 2005;Dobretsov et al, 2007).…”
Section: Introductionmentioning
confidence: 99%